Pengaruh Literasi Keuangan, Inklusi Keuangan, Pengelolaan Keuangan terhadap Kualitas Pelaporan Keuangan serta Kinerja Keuangan UMKM di Kota Surakarta - Muthia Tasya Amalia; Edi Aris Sarwono; Fadjar Harimurti (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to examine the influence of financial literacy, financial inclusion, and financial management on the quality of financial reporting and the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Surakarta. Using a quantitative approach, data were collected through questionnaires distributed to MSME actors who met certain criteria. The analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The findings show that financial literacy, inclusion, and management have a significant effect on the quality of financial reporting, which in turn positively affects financial performance. The quality of financial reporting also acts as a mediating variable in the relationship between financial behavior and MSME performance. This research contributes to the development of MSME financial practices and provides insight for policy makers in enhancing financial capability and reporting standards among MSMEs